Risk factors for paediatric patients with relapsed/refractory NHL who underwent hematopoietic stem cell transplantation: Results of the Turkish paediatric bone marrow transplantation study group - Hazar, Volkan; Kesik, Vural; Karasu, Gülsün; Öztürk, Gülyüz Hanife; Küpesiz, Alphan; Kılıç, Suar Çakı; Ataş, Erman; Uygun, Vedat; Erbey, Fatih; Yılmaz Bengoa, Şebnem; Emir, Suna; Anak, Sema; et al. (Wiley-Blackwell, 2016)
[Abstract Not Available]
WOS: 000384818800392
Keywords: Paediatric Patients; Hematopoietic Stem Cell Transplantation; Refractory NHL